PELAKSANAAN KURIKULUM MERDEKA PADA MATA PELAJARAN PPKN DI SMA NEGERI 2 GOWA - Bakhtiar, Bakhtiar; Agus, Andi Aco; Hilmi, Ulfa (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2024)
This study aims to determine the readiness of teachers fot the implementation of the independent curriculum in Civics subjects at SMA Negeri 2 Gowa. To find out the supporting factors and inhibiting factors when implementing the independent curriculum at SMA Negeri 2 Gowa. This research uses a qualitative approach with the type of research that is descriptive research. The data sourcess used are primary data sources and secondary data sources. The research procedure begins with direct observation in the Gowa 2 Public High School environment, after which it conducts interviews and takes documentation. The collected data will be analyzed using data grouping, data reduction and data presentation techniques. The results of the study showed that: (1) Teacher readiness in the Independent Curriculum In Civics subjects at SMA Negeri 2 Gowa it can be said that they are not sufficiently prepared because they have not prepared the components of teaching materials such as annual programs, semester programs, effective weekly details, time allocations, guidelines assessment, criteria for achieving learning objectives, and projects to strengthen Pancasila student profiles. There are still many preparations that must be made both from the teacher and from the school itself. The independent curriculum education system really needs to be considered in schools so that equity and effectiveness of learning can run in accordance with the ideals of the nation-state, namely educating the life of the nation. (2) There are still many supporting factors and inhibiting factors in implementing the independent curriculum at SMA Negeri 2 Gowa that need to be addressed, one of which is expanding teachers' understanding of the independent curriculum and mastery of technology must also be developed according to the needs of the independent curriculum system. These supporting and inhibiting factors are the initial capital for schools and teachers so that the implementation of the independent curriculum can be carried out perfectly and the learning process can be more effective.